The Lockman Hole Project: new constraints on the sub-mJy source counts from a wide-area 1.4 GHz mosaic. Issue 4 (27th September 2018) - Prandoni, I; Guglielmino, G; Morganti, R; Vaccari, M; Maini, A; Röttgering, H J A; Jarvis, M J; Garrett, M A
ABSTRACT: This paper is part of a series discussing the results obtained in the framework of a wide international collaboration – the Lockman Hole Project – aimed at improving the extensive multiband coverage available in the Lockman Hole region, through novel deep, wide-area, multifrequency (60, 150, 350 MHz, and 1.4 GHz) radio surveys. This multifrequency, multiband information will be exploited to get a comprehensive view of star formation and active galactic nucleus activities in the high-redshift Universe from a radio perspective. In this paper, we present novel 1.4 GHz mosaic observations obtained with the Westerbork Synthesis Radio Telescope. With an area coverage of 6.6 deg 2, this is the largest survey reaching an rms noise of 11 μJy beam −1 . In this paper, we present the source catalogue (∼6000 sources with flux densities S ≳ 55 μ Jy (5σ), and we discuss the 1.4 GHz source counts derived from it. Our source counts provide very robust statistics in the flux range 0.1S1 mJy, and are in excellent agreement with other robust determinations obtained at lower and higher flux densities. A clear excess is found with respect to the counts predicted by the semi-empirical radio sky simulations developed in the framework of the Square Kilometre Array Simulated Skies project. A preliminary analysis of the identified (and classified) sources suggests this excess is to be ascribed to star-forming galaxies, which seem to show a steeper evolution than predicted.